Observations of waves and currents on the fore-reef and reef flat of a coral reef atoll in the South China Sea - Fan, Renfu; Wei, Hao; Mai, Yanfang; Zhang, Lin; Yu, Jitao; Wang, Daoru (Frontiers in Marine Science, 2024)
Understanding the wave and current conditions of coral reef ecosystems is essential for maintaining their health, as many reef processes are controlled by these hydrodynamic conditions. In this study, high-frequency measurements of tides, waves, and currents were made using acoustic, electromagnetic, and pressure instruments over a 28-d period on the fore-reef and reef flat of a coral reef atoll in the South China Sea. The research revealed wave transformation, tidal and wave modulation of flow, and wave setup conditions for the first time at this typical atoll. Three large wave processes dominated by gravity waves (GWs) are observed in the fore-reef. The GWs are significantly attenuated on the reef flat, whereas infragravity (IG) waves strengthened. The tidal modulation of GWs and IG waves on the reef flat is significant when the incident wave height exceeded 1 m. In the fore-reef, the modulation of progressive tidal waves and large waves leads to relatively stronger upper-layer currents, and weak near-bottom currents are primarily attributed to the dissipation of tidal wave energy by the rough coral terrain. In calm conditions, flow variations on the reef flat are modulated by tides, thereby allowing seawater flow to pass through the reef flat during spring tides. Conversely, during periods with large waves, tidal modulation of flow on the reef flat is less significant, and the cross-reef flow velocity increases with increasing incident wave height. The occurrence of wave setup on the reef flat enhances cross-reef flow towards the lagoon. The wave setup is positively linearly correlated with the incident wave height. The magnitude of wave setup is associated with the distance between the measurement sites on the fore-reef and reef flat.